TE EFFECT OF MADRASAH HEADMASTER LEADERSHIP AND ORGANISATION CIRCUMSATANCES ON THE TEACHERS PERFORMANCE IN PONDOK PESANTREN QAMARUL HUDA BAGU PRIGGARATA CENTRAL LOMBOK - ADNAN, MUHAMMAD (Jurnal Magister Manajemen, 2016)
This research is aimed at determining the partial effect and the simultaneous effect of leadership behaviour and organisational circamstances on the performance and at determining the most dominant variable to affect the performance of teacher in Pondok Pesantren Qamarul Huda Bagu Priggarata Central Lombok. This research is associative-causal research where the data were collected from 122 through cencus method and the data were analysed using Multiple Linear Regression. The research showed that leadership and organisation circumstances either partially and simultaneously have positive and significant on the performance. The leadership has the most dominat variable to affect the teacher performace in Pondok Pesantren Qamarul Huda Bagu Priggarata Central Lombok. This research is expected to be as the contribution to the leader in Pondok Pesantren Qamarul Huda Bagu Priggarata Central Lombok in making decision to improve the teacher performance. Keywords: teacher performance, leadership behavior, organisation circumstances